Zimbabwean science students’ perceptions of their classroom learning environments and attitude towards science - Mandina, Shadreck (Richtmann Publishing, 2021)
The purpose of the present study was to examine Zimbabwean junior secondary school students’ perceptions of their classroom environment in science and to investigate relationships between these perceptions and students’ attitudes toward science. The study also aimed to investigate differences in students’ attitudes toward science by gender, school location. Data were collected from 1728 Zimbabwean junior secondary school science students in 10 Kwekwe district schools. Data were collected with an adapted and modified version of the “What is Happening in This Classroom” (WIHIC) instrument and the “Test of Science Related Attitudes” (TOSRA). The study confirmed that the Zimbabwean version of the modified WIHIC is a valid and reliable instrument for measuring the classroom learning environment in the Zimbabwean educational context. Significant differences between students’ perceptions of the actual and preferred learning environment were shown to exist with students tending to prefer a more favorable classroom learning environment than the one which they actually are experiencing. Female students generally hold more positive perceptions of the learning environments than their male counterparts. The findings also revealed that student’ perceptions of the classroom learning environment depending on the schools’ locality, with students in rural schools holding less favorable perceptions than students in urban schools for all seven WIHIC scales. Correlation and regression analyses revealed that students’ perceptions of their learning environment in science were significantly associated with their attitudes.